The Use of Social Media Influencers as a Digital Marketing Strategy in Generation Z - Dwiandini, Afifah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Digital marketing has replaced conventional marketing strategies and has been widely adopted by companies to promote their brands and reach a wider audience. Marketing through the use of Social Media Influencers is a growing trend in the digital era. Gen Z as a tech-savvy generation utilizes the power of social media to get information related to a brand. Gen Z's trust in the expertise of Social Media Influencers is crucial for marketing effectiveness as a digital marketing strategy. This study aims to provide an overview of the use of Social Media Influencers as a digital marketing strategy in Generation Z. This research uses the Systematic Literature Review (SLR) method and systematically identifies and evaluates directly from previous research. The results of this literature review explain that currently, the use of Social Media Influencers has a significant impact on the marketing results carried out by a brand.